2005
DOI: 10.1103/physrevb.72.094519
|View full text |Cite
|
Sign up to set email alerts
|

ABtransition of superfluidHe3in aerogel and the effect of anisotropic scattering

Abstract: We report the results of high-frequency acoustic shear impedance measurements on superfluid 3 He confined in 98% porosity silica aerogel. Using 8.69 MHz continuous wave excitation, we measured the acoustic shear impedance as a function of temperature for the sample pressures of 28.4 and 33.5 bar. We observed the A-B transition on warming in zero magnetic field. Our observations show that the A and B phases in aerogel coexist in a temperature range of about 100 K in width. We propose that differences in the rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 27 publications
6
54
2
Order By: Relevance
“…Additional work at various pressures in zero applied field lead to the same conclusions. 21,68) Based on these experimental results and from the theoretical suggestions of Thuneberg et al, 34) Vicente et al 10) proposed that anisotropic scattering might be the origin for stability of the A-like phase. However, within the context of the free energy expansion, eq.…”
Section: Superfluidmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional work at various pressures in zero applied field lead to the same conclusions. 21,68) Based on these experimental results and from the theoretical suggestions of Thuneberg et al, 34) Vicente et al 10) proposed that anisotropic scattering might be the origin for stability of the A-like phase. However, within the context of the free energy expansion, eq.…”
Section: Superfluidmentioning
confidence: 99%
“…The relative stability of axial and isotropic phases can be determined for IISM from theparameter combinations taken from Table I that give ÁC Aa and ÁC Ba , eqs. (9) and (10). The two phases are thermodynamically so close that they will be difficult to distinguish directly (5 {10%) in specific heat measurements.…”
Section: Superfluidmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the experimental and theoretical studies in the past 10 years revealed that anisotropic disorder has significant influence on the structure of the superfluid phase because of the anisotropic nature of the superfluid itself. Silica aerogels that are homogeneous and isotropic on the scale of the quasiparticle mean-free-path, for example, 150 nm for a 98% porosity aerogel have a dramatic effect destabilizing the A-phase in favor of the B-phase which then fills the entire phase diagram at zero magnetic field [41]. On the other hand anisotropic aerogel samples, stretched during growth by promoting radial shrinkage, were found to stabilize the chiral A-phase at all pressures.…”
Section: Engineering New Phases Of Superlfuid Heliummentioning
confidence: 98%
“…More recent acoustic tracking experiments by Vicente et al [4] and NMR by Osheroff et al [5] (99.3% aerogel) reveal that the A-like phase is in fact stable in a small temperature window near T c at high pressure. Vicente et al suggest that this stabilization is due to the local anisotropic scattering from the aerogel strands.…”
Section: Introductionmentioning
confidence: 99%